The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.3844/ajassp.2006.1853.1858
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Behavior of a Quartz Crystal Microbalance (Qcm) in Contact with Selected Solutions

Abstract: Abstract:A device was constructed to monitor viscosity of solutions using fundamental frequency of 9 MHz and 10 MHz quartz crystal. Piezoelectric quartz crystals with gold electrodes were mounted by O-ring in between liquid flow cell. Only one side of the crystal was exposed to the solutions which were pumped through silicon tube by a peristaltic pump. The measured frequency shift was observed in order to investigate the interfacial behavior of some selected solution in contact with one surface of Quartz Cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The TEER value continued to rise until the 5th day (arrow f: resistance was from 40 to 55 KΩ). The change of weight affecting the quartz resonant frequency and can be detected in the range for about 0.25 μm above the quartz surface in a solution state (Talib et al, 2006). The affected depth was only one-tenth of cells in thickness, the change of frequency can be detected with the cells grown on the surface when cells attached on QCM, and the change of frequency cannot monitor the process of cell metabolism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TEER value continued to rise until the 5th day (arrow f: resistance was from 40 to 55 KΩ). The change of weight affecting the quartz resonant frequency and can be detected in the range for about 0.25 μm above the quartz surface in a solution state (Talib et al, 2006). The affected depth was only one-tenth of cells in thickness, the change of frequency can be detected with the cells grown on the surface when cells attached on QCM, and the change of frequency cannot monitor the process of cell metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Talib et al (2006) reported that different QCM solutions produce different signal frequencies. But there is only a constant distance at the electrode surface in which QCM can detect the change of solution.…”
Section: Qcm Frequency Characterizationmentioning
confidence: 99%
“…If the weight of electrode surface is constant, but liquid viscosity-density change in the solution above the QCM crystal surface will also produce a frequency change. Talib et al (2006) reported that different QCM solutions produce different signal frequencies. But there is only a constant distance at the electrode surface in which QCM can detect the change of solution.…”
Section: Quartz Crystal Microbalance Characterizationmentioning
confidence: 98%
“…5 Equations (1) and (2) are unable to meet specificities of different experiments. Thus density and viscosity will influence the resonance and cause frequency change of QCM in liquid phase.…”
Section: Introductionmentioning
confidence: 99%